Prenatal tobacco and postbirth second‐hand smoke exposure and dental caries in children. Issue 2 (12th April 2021) - Dearing, Bianca A.; Katz, Ralph V.; Weitzman, Michael
Abstract: Objectives: Second‐hand smoke (SHS) exposure has been identified as a risk factor for several childhood health problems including dental caries. The purpose of this study was to examine the association of postbirth SHS exposure and dental caries and to determine whether the association is independent of prenatal tobacco exposure, sugar consumption and dental utilization. Methods: NHANES 2013‐2014 and 2015‐2016 were used to examine the research question in 1733 children, 4‐11 years old with full primary or mixed dentition and serum cotinine levels below 10 ng/mL. Weighted multivariable logistic regression models were developed to examine the independent association between SHS exposure and the prevalence of (i) any dental caries experience and (ii) any decayed teeth. Results: Children exposed to postbirth SHS differed from children not exposed regarding decayed teeth prevalence in the total sample (OR = 1.80, 95% CI: 1.20, 2.71) and mixed dentition (OR = 1.86, 95% CI: 1.20, 2.90) after confounder adjustment. However, no association was found in the primary dentition or between SHS exposure and total caries experience. Conclusions: The findings partially show that postbirth SHS is associated with dental caries in children. However, the inconsistencies in findings across the three samples and between the two outcome measures, dental caries experience and decayed teeth prevalence raise questions regarding the validity of the hypothesis. Further, the findings suggest that postbirth SHS is likely a marker for true causes of dental caries and the association is likely confounded with other factors associated with dental caries.